A matemática financeira na Educação de Jovens e Adultos: possibilidades de ensino e aprendizagem - Casado, Wellison Gomes (2019)
Financial education in school needs to be considered relevant for the training of individuals and their well-being. This study aims to reflect on the teaching of financial mathematics for students of the 5th cycle (8th and 9th grade) of Youth and Adult Education (EJA). We used a qualitative approach and to obtain the data we applied a questionnaire and evaluated a collec- tion of textbooks in the part dedicated to financial mathematics. As the public power was not able to guarantee the quality of the public school and the permanence of the young people in the school, the EJA was created, but the policies for this modality of education were always precarious. Even considering this scenario, we understand that financial mathematics is an important topic and deserves to be highlighted in basic education, especially with EJA stu- dents, because it is a content that is present in students' daily lives. The school does not gua r- antee a critical formation, but it can offer important contributions in this formation of the stu- dent, in diverse contents, especially in financial mathematics. The data show that students' knowledge about financial mathematics, and consequently financial education, is superficial.